AMR parse quality prediction [Source code] - Opitz, Juri (Universität, 2019)
Accuracy prediction for AMR parsing predicts 33 accuracy metrics for a given sentence and its (automatic) AMR parse Abstract (Opitz and Frank, 2019...
Gesehen am 15.07.2019
Keywords: Forschungsdaten; Datenbank